2019
DOI: 10.1136/bmjgh-2019-001787
|View full text |Cite
|
Sign up to set email alerts
|

Invisible medicine sellers and their use of antibiotics: a qualitative study in Cambodia

Abstract: BackgroundGlobal attention to antimicrobial resistance has increased interest in tackling the widespread inappropriate dispensing of antibiotics by informal, for-profit healthcare providers (HCPs). We provide new evidence on an understudied group of informal HCPs: invisible medicine sellers (IMS) who operate without any marked facility. We investigated factors that influence community decisions on which HCPs to purchase medicines from, focusing on reasons for using IMS, and compared different HCPs’ knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 33 publications
(36 reference statements)
1
28
0
Order By: Relevance
“…In Singapore, vested interests were mentioned among pharmaceutical companies in marketing for higher sales of their antibiotics for their own profits; among private practitioners as they make substantial profits when dispensing antibiotics; and among some veterinarians who prescribed antibiotics even when not clinically needed. Our previous research in other settings (i.e., Pakistan and Cambodia) also suggested several considerations and vested interests around antibiotic use which can hinder the control of AMR in the human and animal health sectors [29,30]. For example, it was reported that among doctors there are monetary incentives to prescribe certain antibiotics as these are often negotiated with pharmaceutical companies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In Singapore, vested interests were mentioned among pharmaceutical companies in marketing for higher sales of their antibiotics for their own profits; among private practitioners as they make substantial profits when dispensing antibiotics; and among some veterinarians who prescribed antibiotics even when not clinically needed. Our previous research in other settings (i.e., Pakistan and Cambodia) also suggested several considerations and vested interests around antibiotic use which can hinder the control of AMR in the human and animal health sectors [29,30]. For example, it was reported that among doctors there are monetary incentives to prescribe certain antibiotics as these are often negotiated with pharmaceutical companies.…”
Section: Discussionmentioning
confidence: 93%
“…Third, the AMR policy context represents a policy arena where certain groups engage in "behaviors" that might conflict with the overall goal of controlling AMR. Vested interests are more noticeable than in other health policy areas since different professional groups coexist in the AMR policy arena and there is substantial profit to be made from selling antibiotics [29,30]. In Singapore, vested interests were mentioned among pharmaceutical companies in marketing for higher sales of their antibiotics for their own profits; among private practitioners as they make substantial profits when dispensing antibiotics; and among some veterinarians who prescribed antibiotics even when not clinically needed.…”
Section: Discussionmentioning
confidence: 99%
“…The implicit and critical assumption behind this strategy is that qualified HCPs will prescribe or dispense antibiotics responsibly and that directing patients towards qualified HCPs, and away from unqualified HCPs, will reduce inappropriate use of antimicrobials [15]. However, when HCP professionalism is lacking, boundaries between qualified HCPs and unqualified providers can be blurred [17,18]; for example, qualified providers may routinely fail to follow treatment guidelines [19] or regulations around prescribing [20], and informal providers may demonstrate more empathy towards patients than qualified HCPs [17,21]. We therefore hypothesise that weaknesses in the professionalism of HCPs-including doctors, pharmacists, and nurses-will have an impact on inappropriate use of antibiotics, and we investigate this in two LMIC, Pakistan and Cambodia.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limited benefit and potential harm from antibiotic use, acute diarrhoea is commonly treated with antibiotics in low- and middle-income countries (LMICs) [ 4 6 ]. Recent audits demonstrate that antibiotics are currently the standard treatment in many places in China [ 5 ]. There is a clear relationship between excessive antibiotic prescribing and antibiotic resistance [ 7 , 8 ], which is a major threat to public health as new antibiotic drug development takes a long time and requires very significant investment [ 9 ].…”
Section: Introductionmentioning
confidence: 99%